The equations that are equivalent to the given equation are m - 4 = -7m - 8, -7m - 8 = m - 4 and -8 - 7m = m - 4
The equation is given as
-2m - 5m - 8 = 3 + (-7) + m
Remove the bracket
So, we have
-2m - 5m - 8 = 3 - 7 + m
Evaluate the like terms
So, we have
-7m - 8 = - 4 + m
The above expression can be written as follows
m - 4 = -7m - 8
-7m - 8 = m - 4
-8 - 7m = m - 4
Hence, the equations that are equivalent to the given equation are m - 4 = -7m - 8, -7m - 8 = m - 4 and -8 - 7m = m - 4
Read more about equivalent equations at
https://brainly.com/question/2972832
#SPJ1